Clean Water Using Solar and Wind Opportunities to reach outside the power grid - Olsson, Gustaf (IWA Publishing, 2018)
The aim of Clean Water Using Solar and Wind is to make water professionals aware of the possibilities that solar photo-voltaic (PV) and wind offer to bring, not only clean energy but also clean water to remote and rural areas in Africa and developing Asia as well as in many peri-urban areas in the developing world. These areas are located outside the conventional electric grids and a grid connection is usually not economically feasible. The systems are scalable and can be designed to any size, from the household level to village and community levels. It also means that more capacity can be readily added when demand increases.